Prevalence of hearing loss and impact of hearing handicap on quality of life in elderly in Kelantan - Ting, Jong Hui (Universiti Sains Malaysia, 2015)
The purpose of this research aimed to study the impact of hearing handicap on quality of life (QoL) in elderly in Kelantan. A sample of 50 elderly from Pusat Aktiviti Warga Emas, Rumah Seri Kenangan and Audiology Clinic, Hospital USM was surveyed through hearing assessment and using questionnaires. The instruments were based upon demographic profile, Malay version Short Form 36 Health Survey (SF-36) and Malay version Hearing Handicap Inventory for the Elderly (HHIE). Malay version SF-36 assessed the QoL while the HHIE assessed the hearing handicap suffered by the elderly. The data was coded and analyzed using MedCalc and Pearson’s correlation. Results show that all three categories (average ear, better ear and worse ear hearing loss) are correlated with the HHIE scores. However, the degree of hearing loss do not all correlate with HHIE scores. Only the better ear with moderate degree of hearing loss and worse ear with mild degree of hearing loss correlate with HHIE scores. The results also show that there is a correlation between HHIE and all domains of SF-36, physical composite summary (PCS) and mental composite summary (MCS), except physical functioning (PF). Since a reduction of QoL was correlated with hearing handicap, reduction in hearing handicap should be treated seriously as it showed reduction in the QoL of elderly. Thus, elderly patient should seek for proper hearing assessment when they came across with hearing difficulties.